2021
DOI: 10.3389/fphar.2021.666432
|View full text |Cite
|
Sign up to set email alerts
|

Network Pharmacology-Based Validation of the Efficacy of Huiyangjiuji Decoction in the Treatment of Experimental Colitis

Abstract: Ulcerative colitis (UC) is the major type of inflammatory bowel disease (IBD) characterized by an overactive immune responses and destruction of the colorectal epithelium with intricate pathological factors. In China, Huiyangjiuji decoction (HYJJ) has been widely administered against inflammation, but the underlying mechanical mechanisms are not known. A murine model of colitis was established by orally feeding 4% dextran sodium sulfate for 5 days. Intestinal organoids (IOs) were treated with TNFα (Tumor necro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 59 publications
(65 reference statements)
1
6
0
Order By: Relevance
“…Furthermore, QZZTD inhibited PI3K-AKt pathway activation, reduced inflammation, and alleviated UC. The aforementioned study also yielded the same results, revealing that TCM treatment of UC may mainly produce efficacy by regulating the PI3K-Akt signaling pathway ( Liu J. et al, 2021 ; Liu X. et al, 2021 ; Song et al, 2021 ; Yu et al, 2021 ).…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…Furthermore, QZZTD inhibited PI3K-AKt pathway activation, reduced inflammation, and alleviated UC. The aforementioned study also yielded the same results, revealing that TCM treatment of UC may mainly produce efficacy by regulating the PI3K-Akt signaling pathway ( Liu J. et al, 2021 ; Liu X. et al, 2021 ; Song et al, 2021 ; Yu et al, 2021 ).…”
Section: Discussionsupporting
confidence: 58%
“…It revealed that Gegen Qinlian Decoction ameliorates inflammation via downregulating the epidermal growth factor receptor (EGFR)/PI3K/AKT signaling pathway and pro-inflammatory cytokines ( Liu X. et al, 2021 ). Studies using network pharmacology combined with in vivo and ex vivo experiments and RNA-sequencing methods have similarly confirmed that genes downregulated by drugs were enriched in inflammation-related pathways ( Yu et al, 2021 ). Additionally, there are research studies that use the same approach to study drugs for different diseases, such as resveratrol, which can alleviate COVID-19–related inflammation ( Xiao et al, 2021 ).…”
Section: Discussionmentioning
confidence: 94%
“…When it comes to the regulation of ROS, we observed that macrophages isolated from the DSS group aggravated the ROS production in intestinal stem cells due to the release of inflammation-promoting cytokines by macrophages ( Yan et al, 2021 ; Yu et al, 2021 ). Since intestinal stem cells are responsible for epithelial replenishment, excessive ROS-induced cell death would exacerbate the compromised epithelial integrity during colitis.…”
Section: Discussionmentioning
confidence: 99%
“…The experimental results also show that Zuojin pill is effective in the treatment of chronic atrophic gastritis ( Tong et al, 2021 ). In the Huiyangjiuji decoction on the molecular mechanism of the UC treatment study, the target genes of the validation pathway were found, induced by pathogen infection and tumor-related enrichment in frontal pathways, in vitro experiments also confirmed Huiyangjiuji decoction of IL-2, IL-10, and IL-12 interleukins have an obvious inhibitory effect, thus inhibiting the further development of intestinal inflammation ( Yu et al, 2021 ). In other studies, nine active components of Xianglian pill that may have anti-inflammatory effects which were identified through the literature review, and the treatment of ulcerative colitis was mainly through regulating key pathways of the immune system, reducing mucosal inflammation, and achieving anti-inflammatory effects ( Liu et al, 2021b ).…”
Section: Application Of Network Pharmacology In the Treatment Of Ulce...mentioning
confidence: 92%